The first two decades of CREB-memory research: data for philosophy of neuroscience - John Bickle (AIMS Neuroscience, 2021)
I recount some landmark discoveries that initially confirmed the cyclic AMP response element-binding (CREB) protein-memory consolidation and allocation linkages. This work constitutes one of the successes of the field of Molecular and Cellular Cognition (MCC) but is also of interest to philosophers of neuroscience. Two approaches, “mechanism” and “ruthless reductionism”, claim to account for this case, yet these accounts differ in one crucial way. I explain this difference and argue that both the experiment designs and discussions of these discoveries by MCC scientists better fit the ruthless reductionist's account. This conclusion leads to further philosophical discussion about how discoveries in cellular/molecular neurobiology integrate with systems neuroscience findings.